An experimental and numerical analysis of the performances of a Wankel steam expander. (September 2017) - Francesconi, Marco; Caposciutti, Gianluca; Antonelli, Marco
Abstract: In the last decades, the energy market increased its interest towards the smart grids and electrically isolated systems. These systems utilize small size power generator, which often feature volumetric expanders that are very robust and reliable for a wide range of operative conditions. In this work a study that focuses on a Wankel volumetric expander was carried out. In order to predict the extractable specific work from the expander, a thermodynamic lumped parameters numerical model was developed. The model was validated by means of experimental data obtained using water steam as working fluid. The experimental results encouraged the need to improve the research of this expander, as well as the capability of the numerical model to predict the effective performances of the device.